Finite Care in a World of Infinite Need - Hauerwas, Stanley (Christian scholar's review, 2009)
Stanley Hauerwas explores the ways in which the fear of death, or more generally the fear of human limitation, shapes the discourse in medical ethics insofar as often the underlying presumption is that medicine’s ultimate aim is to put an end to human limitation – even death. Drawing on the work of Paul Ramsey, Hauerwas examines the complexity involved in attempting to do medical ethics when “we do not make explicit or acknowledge the forces that are ordering our priorities.” In a free market economy, Hauerwas suggests, justice with regards to medical practices is determined according to the individual’s ability to pay. In other words, doctors can practice medicine “justly” if they are limited to seeing patients who can pay for the care. But this conception of justice does not take into account the patients who are unable to see the doctor because of their inability to pay. He concludes by suggesting the Christian community can provide a witness to the medical community first by accepting human finitude as a gift, and second by existing as a community whose justice is found decisively in the care of the other—regardless of their ability to offer compensation. Mr. Hauerwas is the Gilbert T. Rowe Professor of Theological Ethics at Duke University.